Toughness enhancement of polymers - Hassan, Azman (2002)
Toughness is an important mechanical property and often the deciding factor in materials selection. The continuing growth in the use of plastics for engineering and other applications is due in no small measure to the development, during the past five decades, of new and tougher plastics materials.